Pengaruh Efikasi Diri Berwirausaha terhadap Niat Berwirausaha Masyarakat Desa - Ahmad Sya Roni; Sanaji Sanaji (Jurnal Ilmu Manajemen, 2020)
Sidoarjo is a district with the most number of small and medium businesses in Indonesia, there reach 171,264 business units. The details, micro-business 154,891 units, small and medium businesses 154 units, and large businesses 16,000 units. One of the industrial centers in the city of Sidoarjo is the Tanggulangin leather craft industry. Most of the people of Kedensari village have the expertise and skills to create a product that can be marketed and has a high selling value. The purpose of this study was to examine and analyze the entrepreneurial self-efficacy towards the entrepreneurial intentions of the Kedensari village community, Tanggulangin sub-district, Sidoarjo. This research is causality research with a quantitative approach. The sample collection technique uses 100 samples saturated with the number of respondents in a citizen of Kedensari. The research method is using a simple linear regression with the use of the SPSS 23 program for windows. Whereas, hypothesis testing using t-test showed that self-efficacy partially has a significant influence on interest entrepreneurship.